2017
DOI: 10.1007/s12094-017-1703-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after whole brain radiotherapy compared with radiosurgery of the tumor bed: results from a randomized trial

Abstract: Despite higher symptom burden after WBRT attributed to the side effects of RT (such as appetite loss, drowsiness, and hair loss), global health status, physical functioning, and future uncertainty favored WBRT compared with SRT-TB. This may be related to the compromised brain tumor control with omission of WBRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Our study has several limitations. First, although the examination compliance in our study population was better (85% at 4 months) than that reported in other studies (59-73% at 2-4 months) [6,8,11,[21][22][23], there were patients who could not perform the follow up examinations. Second, this study was unable to perform multivariate analysis that considers confounding factors related to cognitive dysfunction such as opioids [24], chemotherapy [25], surgery, etc..…”
Section: Discussioncontrasting
confidence: 75%
“…Our study has several limitations. First, although the examination compliance in our study population was better (85% at 4 months) than that reported in other studies (59-73% at 2-4 months) [6,8,11,[21][22][23], there were patients who could not perform the follow up examinations. Second, this study was unable to perform multivariate analysis that considers confounding factors related to cognitive dysfunction such as opioids [24], chemotherapy [25], surgery, etc..…”
Section: Discussioncontrasting
confidence: 75%
“…In contrast, Cheng et al reported early cognitive impairment at one month after WBI, likely due to the frontal lobe damage [12] . Between these opposing positions, Kepka et al [13] supported that the omission of WBI after post-operative SRS delivered to the tumor bed affected the quality of life (QoL) and survival rates due to a poor sub-clinical disease control. These data have also been observed by Aoyama et al [14] in a prospective study.…”
Section: Introduction/rationalementioning
confidence: 99%
“…Irrespective of these different statistical scenarios, systemic treatment significantly improved survival. At present, many patients receive other types of brain irradiation, such as stereotactic radiosurgery (SRS), which may provide a better therapeutic ratio [16][17][18]. However, sophisticated local treatment is less appealing if followed by best supportive care (BSC) rather than systemic therapy.…”
Section: Introductionmentioning
confidence: 99%